EFEKTIVITAS TERAPI MUSIK DALAM MENGURANGI NYERI PERSALINAN PADA WANITA PRIMIPARA : LITERATURE REVIEW - Arindra Dwi Angraini; Dianatika Azmmi; Dinda Zulyarnis; Fatmawati Wati; Rohayati (AKPER Pasar Rebo, 2021)
Background :In pregnant women, labor pain may be the main thing to worry about, especially in primiparous women. Labor pain that is so increased, can hamper the delivery process due to disruption of body homeostasis. Objective : To determine the effectiveness of giving music therapy to primiparous pregnant women to reduce labor pain. Method : The method of writing this article is through a simple approach. Searching the article database using PubMed and Science Direct resulted in 6 articles. Results : The administration of music therapy to primiparous women during labor was quite effective in reducing pain. The results of pain reduction between the group given and the control group or without the intervention were quite significant. Music therapy not only reduces labor pain but also affects the anxiety of the mother during labor. Conclusion : Music therapy can reduce labor pain and reduce anxiety in primiparous women.